2003
DOI: 10.1080/0963828031000137135
|View full text |Cite
|
Sign up to set email alerts
|

Past and future use of the ICF (former ICIDH) by nursing and allied health professionals

Abstract: Although former and present use prove to be valuable, the level of detail needed for a richer description of the functioning of a patient does not yet exist within the ICIDH nor within the ICF. This and other arguments are given for the innovation process of the ICF and the need for the development of a (multidisciplinary) clinical modification, the ICF-CM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 6 publications
0
12
0
1
Order By: Relevance
“…This has sometimes been termed the WHO model (WHO, 2001), the ICIDH or ICIDH-2 (WHO, 1999). The framework has been applied to many aspects of speech-language pathology including the scope of practice of the profession American SpeechLanguage-Hearing Association (ASHA, 2001), national data collection (Heerkens, van der Brug, Napel, & van Ravensburg, 2003) framing assessments and interventions (e.g., Brush, Threats, & Calkins, 2003;Eadie, 2001;Hartley & Wirz, 2002;Le Dorze & Brassard, 1995;Ma & Yiu, 2001;Raaijmakers, Dekker, Dejonckere, & van der Zee, 1995;Ross & Wertz, 1999;Worrall & Frattali, 2000;Yaruss, 1998), measuring clinical and research outcomes (Enderby & Johns, 1997;Frattali, 1998;Worrall & Yiu, 2000) and researching the relative contribution of communication to quality of life (Cruice, Worrall, Hickson, & Murison, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…This has sometimes been termed the WHO model (WHO, 2001), the ICIDH or ICIDH-2 (WHO, 1999). The framework has been applied to many aspects of speech-language pathology including the scope of practice of the profession American SpeechLanguage-Hearing Association (ASHA, 2001), national data collection (Heerkens, van der Brug, Napel, & van Ravensburg, 2003) framing assessments and interventions (e.g., Brush, Threats, & Calkins, 2003;Eadie, 2001;Hartley & Wirz, 2002;Le Dorze & Brassard, 1995;Ma & Yiu, 2001;Raaijmakers, Dekker, Dejonckere, & van der Zee, 1995;Ross & Wertz, 1999;Worrall & Frattali, 2000;Yaruss, 1998), measuring clinical and research outcomes (Enderby & Johns, 1997;Frattali, 1998;Worrall & Yiu, 2000) and researching the relative contribution of communication to quality of life (Cruice, Worrall, Hickson, & Murison, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In a differing vantage point, Heerkens, VanDerBrug, Ten Napel, and Van Ravensberg (2003) described the use of the ICIDH, the precursor of the ICF, by allied health and nursing professions in the Netherlands. These authors concluded that the level of detail needed for a richer description of the functioning of a patient does not yet exist within the ICIDH or the ICF classification systems.…”
Section: Nursingmentioning
confidence: 99%
“…The findings of the anamnesis corroborate the critical constants of own professionals before the shortage of methods used to analyze the function and activities of patients daily life. This fact is due to the restriction of classical analysis focused on the disease, in which the human functionality and activities of daily life are under valued 16 . Similarly, the techniques applied in the physical examination suggest the original idea of physical therapy as a health area that studies, prevents and treats kineticfunctional disorders that becomes from changes in organs and systems of the human body.…”
Section: Discussionmentioning
confidence: 99%